2007
DOI: 10.1021/ac070403i
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Genosensor Based on Polyaniline

Abstract: Avidin-modified polyaniline (PANI) electrochemically deposited onto a Pt disk electrode has been utilized for direct detection of Escherichia coli by immobilizing a 5'-biotin-labeled E. coli probe (BdE) using a differential pulse voltammetric technique in the presence of methylene blue as a DNA hybridization indicator. Depending on the target sample and the sonication time, this BdE-avidin-PANI bioelectrode can be utilized to electrochemically detect a complementary target probe (0.009 ng/microL), E. coli geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…Arora et al reported an electrochemical approach combining methylene blue and a conducting polymer-based detection, which afforded detection limits for Escherichia coli gDNA of 3.5 fM. Importantly, extensive gDNA fragmentation (estimated size of 20 bp) was the key aspect not only on sensitivity but also on the response speed (Arora et al 2007). Another approach comprised the use of blocking oligonucleotides whose function was to prevent gDNA target re-hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…Arora et al reported an electrochemical approach combining methylene blue and a conducting polymer-based detection, which afforded detection limits for Escherichia coli gDNA of 3.5 fM. Importantly, extensive gDNA fragmentation (estimated size of 20 bp) was the key aspect not only on sensitivity but also on the response speed (Arora et al 2007). Another approach comprised the use of blocking oligonucleotides whose function was to prevent gDNA target re-hybridization.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the electropolymerization of biotin derivatives, another strategy consists in the covalent binding of one of the affinity partners onto polyaniline films. For instance, the anchoring of a biotinylated 20-mer oligonucleotide specific to Escherichia coli on an avidin-grafted polyaniline film led to an efficient electrochemical genosensor for E. coli cells without using PCR amplification [111]. The hybridization of E. coli cell lysate was detected by differential pulse voltammetry in the presence of methylene blue.…”
Section: Noncovalent Binding By Affinity Interactions With the Electrmentioning
confidence: 99%
“…The hybridization studies of PNA-GOPS/ITO and PNA/ Fe 3 O 4 -GOPS/ITO electrodes have been performed by monitoring SWV of methylene blue as redox indicator [22,[44][45]. Methylene blue gets converted into leukomethylene blue at À0.35 V and is further reduced into methylene blue at À0.42 V (Figure 4a) [46].…”
Section: Electrochemical Response Studiesmentioning
confidence: 99%